Law enforcement of fishery crime by the navy (The conflict between business and law enforcement) - Subekti, Imam; Myrantika, Annie; Pandia, Harun (2017)
Purpose - This study adds to the limited body of empirical evidence on authority of the Navy Officers as Fisheries Criminal Investigators which has been expressly regulated in the provisions of Article 73 paragraph (1) of Law 45, 2009, concerning Amendment of Law 31, 2004, concerning Fisheries and implemented pursuant to the laws and regulations applicable in Indonesia as well as international law in UNCLOS 1982.Methodology - The theoretical models of compliance behavior tested with the basic deterrence model, which focuses on the certainty and severity of sanctions as key determinants of compliance.Findings - The results of the empirical analysis provide additional evidence on the relationship of deterrence and legitimacy to compliance.The findings are also used to draw implications for compliance policy for regulated fisheries.